Procedural Aspects of Handling the Electronic Evidence: the Ukrainian Context - O. V. Manzhai; A. O. Potylchak; I. V. Manzhai (Law and Safety)
The article analyzes the procedural aspects of the seizure, recording and analysis of electronic traces of the crime. Some statistical data on persons convicted under Art. 361-363-1 of the Criminal Code of Ukraine. The history of formation of the institute of electronic proofs is considered. The theoretical basis for understanding the essence of electronic evidence is outlined. It is noted the lack of regulation of the issue of working with electronic evidence in criminal proceedings. Some procedural aspects of electronic document review are revealed and some examples are given. The authors believe that the nature of electronic data, the mechanism of their formation allow us to consider them as a separate type of evidence, and the forms of their fixation defined in the current Ukrainian legislation are not perfect at present. It is proved that when working on the network, law enforcement agencies can record only the projection of the original electronic document as a separate case of electronic evidence, and such a projection can not be considered the original. The method of recording electronic evidence in the framework of covert investigative (search) action to remove information from electronic information systems is analyzed. Some bills aimed at normalizing the peculiarities of working with electronic traces of crimes in criminal proceedings are studied.